Imagined Steps: Mental Simulation of Coordinated Rhythmic Movements Effects on Pro-sociality - Cross, Liam; Atherton, Gray; Wilson, Andrew D.; Golonka, Sabrina (Frontiers in Psychology, 2017)
Rhythmically coordinating with a partner can increase pro-sociality, but pro-sociality does not appear to change in proportion to coordination success, or particular classes of coordination. Pro-social benefits may have more to do with simply coordinating in a social context than the details of the actual coordination (Cross, Wilson, & Golonka, 2016). This begs the question, how stripped down can a coordination task be and still affect pro-sociality? Would it be sufficient simply to imagine coordinating with others? Imagining a social interaction can lead to many of the same effects as actual interaction (Crisp & Turner, 2009). We report the first experiments to explore whether imagined coordination affects pro-sociality similarly to actual coordination. Across two experiments and over 450 participants, mentally simulated coordination is shown to promote some, but not all, of the pro-social consequences of actual coordination. Imagined coordination significantly increased group cohesion and deindividuation, but did not consistently affect cooperation.